2022
DOI: 10.3389/fphar.2022.814814
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of EIF2 Signaling, Glycolysis, and Dopamine Secretion in Form-Deprived Myopia in Response to 1% Atropine Treatment: Evidence From Interactive iTRAQ-MS and SWATH-MS Proteomics Using a Guinea Pig Model

Abstract: Purpose: Atropine, a non-selective muscarinic antagonist, effectively slows down myopia progression in human adolescents and several animal models. However, the underlying molecular mechanism is unclear. The current study investigated retinal protein changes of form-deprived myopic (FDM) guinea pigs in response to topical administration of 1% atropine gel (10 g/L).Methods: At the first stage, the differentially expressed proteins were screened using fractionated isobaric tags for a relative and absolute quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 116 publications
1
10
0
Order By: Relevance
“…Our data also showed an imbalance towards down-regulated proteins, especially concerning FhNEJ extracts upon MPSIEC co-culture, which has been observed in similar studies (e.g., [ 33 , 34 ]). This fact suggests that silencing of protein expression could be faster than its induction in FhNEJ after a short time of stimulation with host tissues, which could also be related to the turnover and/or shedding mechanisms that take place on the FhNEJ surface shortly after excystment as part of their immune evasion strategies [ 35 , 36 ].…”
Section: Resultssupporting
confidence: 88%
“…Our data also showed an imbalance towards down-regulated proteins, especially concerning FhNEJ extracts upon MPSIEC co-culture, which has been observed in similar studies (e.g., [ 33 , 34 ]). This fact suggests that silencing of protein expression could be faster than its induction in FhNEJ after a short time of stimulation with host tissues, which could also be related to the turnover and/or shedding mechanisms that take place on the FhNEJ surface shortly after excystment as part of their immune evasion strategies [ 35 , 36 ].…”
Section: Resultssupporting
confidence: 88%
“…Zhu et al, 2022 carried out a proteomics experiment in guinea pigs to identify new proteins and pathways of retinal cells that could be affected by atropine administration [36]. The analysis revealed that Eukaryotic Initiation Factor 2 (EIF2) signaling and glycolysis are significantly affected by atropine.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The list of the plants producing the alkaloids and their applications in the ophthalmology field are also reported. [36]. The analysis revealed that eukaryotic initiation factor 2 (EIF2) signaling and glycolysis are significantly affected by atropine.…”
Section: Exploitation Of Plant Alkaloids In Ophthalmologymentioning
confidence: 99%
“…In recent years, numerous studies on retinal regulatory mechanisms have detailed the various molecular mechanisms involved in the development of FDM, including neurotransmitters, noncoding RNAs, and cellular functions . Due to advances in biological techniques, proteomic analysis has become a viable approach to reveal the underlying molecular mechanisms of myopia in their entirety. We found multiple studies identifying molecules and pathways associated with metabolism in the myopic retina, including insulin expression, apo A1 expression, glycolysis, and mitochondrial metabolism . However, the molecular mechanism of retinal metabolic dysregulation due to myopia is still elusive.…”
Section: Introductionmentioning
confidence: 99%